Catalytic reduction of 4-nitrophenol with gold nanoparticles stabilized by large-ring cyclodextrins. (25th November 2020) - Noël, Sébastien; Bricout, Hervé; Addad, Ahmed; Sonnendecker, Christian; Zimmermann, Wolfgang; Monflier, Eric; Léger, Bastien
Abstract : Au NP, stabilized by large-ring cyclodextrins, proved to be efficient for the catalytic reduction of 4-nitrophenol. Abstract : The synthesis of gold nanoparticles stabilized in an aqueous phase by cyclodextrins (CD) was performed. The solvent-dispersed nanoparticles were characterized by transmission electron microscopy, UV-vis spectroscopy and dynamic light scattering analysis. Nanoparticles stabilized with large-ring CD composed of 9 or more glucose units showed a broader distribution of sizes and a larger hydrodynamic diameter compared to those stabilized with α-CD, β-CD and γ-CD. Gold nanoparticles stabilized by large-ring CD efficiently reduced 4-nitrophenol to 4-aminophenol with higher reaction rates compared to those stabilized by α-CD. NMR analysis proved that no complex formation between 4-nitrophenol and the large-ring CD occurred. The catalytic activities obtained with gold nanoparticles stabilized by large-ring CD were comparable to those observed with β-CD and γ-CD confirming their suitability for an efficient stabilization of catalytically active nanoparticles.